Profiles, Psychology and Satisfaction of Anglers on Fishing Facilities of Saltwater Pond - Mohd Jirey Kumalah; Mohamad Pirdaus Yusoh; Rosmiza M. Z.; Muhammad Fuad Abdullah; Nurhazliyana Hanafi; Normah Abdul Latip (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Purpose: This research looked at visitor characteristics as well as angler satisfaction with recreational fishing facilities and services at the Ko-Nelayan Laya-Laya Marine Fishing Pond (KPIMKL) in Tuaran, Sabah. Theoretical Framework: Recreational fishing has a lot of potential in Sabah since there are so many natural areas to fish in, such the sea, rivers, and ponds. Although there have been researches on recreational fishing in ponds, particularly artificial and freshwater ponds, no studies on saltwater ponds have been done. Design/Methodology/Approach: The study design is exploratory and descriptive, using a quantitative approach. Qualitative approaches through in-depth interviews with KPIMKL entrepreneurs and indirect interviews with chosen respondents, are also used in this study. The survey included 105 people who were chosen at random. Findings: The finding showed that the visitor profiles of the respondents include repeat visitation and group visitation, fishing duration of 5 - 6 hours, utilising private automobile, major source of information is social media, and the attraction elements are the diversity of fishing ponds and sizes of fish. Furthermore, the majority of respondents have participated in KPIMKL-organised contests, particularly in the Big Game category. Visitors were generally satisfied, as 10 of the 17 attributes for facilities and services provided at KPIMKL received a “very high” mean score (including surau facilities, rest huts, and food stalls), 6 received a “high” mean score (including toilets, complaints and information spaces, as well as fishing fees), and only one received a “moderate” mean score (the rubbish bins facility). Research Practical and Social Implication: In summary, the recreational fishing study at this saltwater fishing pond will help stakeholders, particularly fisheries department and fishing pond operators to be more dedicated and proactive in ensuring the quality of fishing services and facilities is always at its best.